Antioxidant Activities of Streptomyces sp. strain MUSC 14 from Mangrove Forest Soil in Malaysia. (11th March 2020) - Kemung, Hefa Mangzira; Tan, Loh Teng-Hern; Chan, Kok-Gan; Ser, Hooi-Leng; Law, Jodi Woan-Fei; Lee, Learn-Han; Goh, Bey-Hing
Abstract : The mangrove ecosystem of Malaysia remains yet to be fully explored for potential microbes that produce biologically active metabolites. In the present study, a mangrove-derived Streptomyces sp. strain MUSC 14 previously isolated from the state of Pahang, Malaysia Peninsula, was studied for its potential in producing antioxidant metabolites. The identity of Streptomyces sp. strain MUSC14 was consistent with the genotypic and phenotypic characteristics of the Streptomyces genus. The antioxidant potential of Streptomyces sp. strain MUSC 14 was determined through screening of its methanolic extract against sets of antioxidant assays. The results were indicative of Streptomyces sp. strain MUSC 14 displaying strong antioxidant activity against ABTS, DPPH free radicals and metal chelating activity of 62.71 ± 3.30%, 24.71 ± 2.22%, and 55.82 ± 2.35%, respectively. The result of ferric reducing activity measured in terms of dose was equivalent to 2.35–2.45  μ g of positive control ascorbic acid. Furthermore, there was a high correlation between the total phenolic content and the antioxidant activities with r  = 0.979, r  = 0.858, and r  = 0.983 representing ABTS, DPPH, and metal chelation, respectively. Overall, the present study suggests that Streptomyces sp. strain MUSC 14 from mangrove forest soil has potential to produce antioxidant metabolites that can be further exploited for therapeutic application.